Ibn – Jenni’s method in the book (Alloma’ in Arabic) - Al-reqeb, Mohammad Salman (Journal of Arabic Language Sciences and Literature, 2022)
The ancient linguistic heritage is still brightening, leads us, gives us science, but in a different reading which does not separate from the origin to sound what the ancient authors reached and achieved in the language as (Seebawieh) and (Ibn Jenni), and other language burgees; to show some of their styles in authoring and writing.The ancient and modern research in linguistic science is still wide open, and while reading the book of (Alloma’ fi Al arabiah) for Al-shiekh Abi Al-Fath Othman bin Jenni, I saw that it was an educational book, which does contain all the doors only, but it was flashes and signs that Ibn Jenni meant to facilitate and educate. Ibn Jenni’s book took variety of subjects in Syntax and Morphology and linguistic issues.
Keywords: Ibn Jenni; Alloma’ in Arabic; Syntax and Morophology